Maritime policy: administrative and legal measurement in the context of the realization of the Maritime Doctrine of Ukraine - Mishehlina, Khrystyna; Мишеглина, Кристина (Одеса : Гельветика, 2019)
The article is devoted to the research of the main directions and the current state of realization of state maritime policy from the standpoint of the study of administrative – legal mechanisms and means of its realization in the context of the approved the Maritime Doctrine of Ukraine for the period up to 2035. The modern tendencies and directions of the state maritime policy are determined. Some aspects of realization of maritime policy of Ukraine are considered. The article deals with the mechanisms of formation and implementation of maritime policy within the framework of national maritime jurisdiction. The author outlines the main conceptual directions of the development of the maritime policy of Ukraine and highlights its institutes. The Maritime Doctrine of Ukraine is the basis for the formation and implementation of the maritime policy of Ukraine. The achievement of the maritime policy goals and objectives and ensuring national interests in the coastal waters of Ukraine for a great extend depends upon the effectiveness of the proper implementation means. The means of implementing the provisions of the Maritime Doctrine is undoubtedly based on the executive authorities activities within the frameworks of public administration in the relevant sphere. Such administration is carried out in forms and though the methods, which are regulated by administrative law. At the same time, the national state in the public administration of the maritime area is bound with the rules and requirements of international legal acts on the law of the sea, starting with the general provisions on the State’s jurisdiction in the coastal waters, ending up with specific requirements regarding the acting procedures of the respective state authorities. Therefore, in order to form the theoretical basis for updating and improving the current legislation and practice of public administration in the maritime sphere, the topic of work is the study of administrative and legal means of realization of the Maritime Doctrine of Ukraine. Статтю присвячено дослідженню основних напрямів та сучасного стану реа- лізації державної морської політики з позиції дослідження адміністративно-пра- вових механізмів та засобів її реалізації у контексті затвердженої Морської док- трини України на період до 2035 р. З метою формування теоретичного підґрунтя оновлення та вдосконалення діючого законодавства і практики публічного адмі- ністрування морської сфери темою статті було обрано дослідження адміністра- тивно-правових засобів реалізації Морської доктрини України. Було визначено сучасні тенденції та напрямки державної морської політики. Розглянуто окремі аспекти реалізації морської політики України. У статті досліджено механізми формування та реалізації морської політики у межах національної морської юрисдикції. Автором виокремлено основні концептуальні напрямки розвитку морської політики України та розглянуто її інститути. Морська доктрина України є основою для формування та реалізації морської політики України. Від ефектив- ності засобів її реалізації безпосередньо залежить досягнення цілей та завдань морської політики та забезпечення національних інтересів у прибережних водах України. Основою засобів реалізації положень Морської доктрини є діяль- ність органів виконавчої влади у рамках публічного адміністрування відповід- ної сфери. Таке адміністрування здійснюється у формах та за допомогою мето- дів, врегульованих адміністративним правом. При цьому, держава у здійсненні публічного адміністрування у морській сфері зв’язана правилами та вимогами міжнародно-правових актів з морського права, починаючи із загальних поло- жень щодо юрисдикції держави у прибережних водах, закінчуючи специфічними вимогами щодо порядку діяльності відповідних суб’єктів владних повноважень.
Mishehlina K. Maritime policy: administrative and legal measurement in the context of the realization of the Maritime Doctrine of Ukraine / K. Mishehlina // Lex Portus : юрид. наук. журн. / редкол. : С. В. Ківалов (голов. ред. ради), Б. А. Кормич (голов. ред.), І. В. Сафін (заст. голов. ред.), Т. В. Аверочкіна (наук. ред., відп. секр.) [та ін.] ; НУ "ОЮА", ГО "МА Святий Миколай". - Одеса : Видавничий дім «Гельветика», 2019. - № 1. – C. 36 – 49
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; морська політика; морська політика України; державна морська політика; Морська доктрина України; Морская доктрина Украины; морская политика; maritime policy and its implementation; maritime policy of Ukraine; state maritime policy, formation of maritime policy; Ukranian maritime doctrine and its implementation